Role of DNA Methylation Profile in Diagnosing Astroblastoma: A Case Report and Literature Review - Petruzzellis, Giuseppe; Alessi, Iside; Colafati, Giovanna Stefania; Diomedi-Camassei, Francesca; Ciolfi, Andrea; Pedace, Lucia; Cacchione, Antonella; Carai, Andrea; Tartaglia, Marco; Mastronuzzi, Angela; Miele, Evelina (Frontiers in Genetics, 2019)
Astroblastoma is a rare tumor of the central nervous system (CNS) with uncertain clinical behavior. Recently, DNA methylation profiling has been shown to provide a highly robust and reproducible approach for the classification of all CNS tumors across different age groups. By using DNA methylation profiling, a subset of CNS high-grade tumors with astroblastoma-like morphology characterized by the meningioma 1 gene (MN1) rearrangements, has been identified; they were termed "CNS high-grade neuroepithelial tumors with MN1 alteration" (CNS-HGNET-MN1). Here, we describe a case of CNS-HGNET-MN1 diagnosed by DNA methylation profiling, using Illumina Infinium HumanMethylationEPIC BeadChip (EPIC), that offers the opportunity to conduct a brief literature review. The patient presented with an episode of partial seizures involving the right hemisoma. A gross total resection was performed. No other treatment was proposed in light of the histological and molecular findings. After 21 months, the patient is disease-free in good clinical conditions. Also in view of this case, we recommend DNA-methylation profiling as an important tool for diagnosis and more effective patient stratification and management.